Lysophosphatidic Acid Receptor 1 Specifically Labels Seizure-Induced Hippocampal Reactive Neural Stem Cells and Regulates Their Division - Valcárcel-Martín, Roberto; Martín-Suárez, Soraya; Muro-García, Teresa; Pastor-Alonso, Oier; Rodríguez de Fonseca, Fernando; Estivill-Torrús, Guillermo; Encinas, Juan Manuel (Frontiers in Neuroscience, 2020)
A population of neural stem cells (NSCs) dwelling in the dentate gyrus (DG) is able to generate neurons throughout adult life in the hippocampus of most mammals. These NSCs generate also astrocytes naturally and are capable of generating olygodendrocytes after gene manipulation. It has been more recently shown that adult hippocampal NSCs after epileptic seizures as well as subventricular zone NSCs after stroke can give rise to reactive astrocytes (RAs). In the hippocampus the induction of seizures triggers the conversion of NSCs into reactive NSCs (React-NSCs) characterized by a drastic morphological transformation; abnormal migration and massive activation or entry into the cell cycle to generate more React-NSCs that ultimately differentiate into RAs. In the search for tools to investigate the properties of React-NSCs we have explored the LPA1-GFP transgenic line of mice in which hippocampal NSCs are specifically labeled due to the expression of lysophosphatidic acid receptor 1 (LPA1). We first addressed the validity of the transgene expression as true marker of LPA1 expression and then demonstrated how after seizures, LPA1-GFP labeled exclusively React-NSCs for several weeks. Then React-NSCs lost LPA1-GFP expression as neurons of the granule cell layer started to express it. Finally, we used knock-out for LPA1 transgenic mice to show that LPA1 plays a functional role in the activation of React-NSCs. Thus, we confirmed that LPA1-GFP expression is a valid tool to study both NSCs and React-NSCs and that the LPA1 pathway could be a target in the intent to preserve NSCs after seizures.